Hematological indices in elite cyclists - Schumacher, Y. O.; Jankovits, R.; Bultermann, D.; Schmid, A.; Berg, A. (Scandinavian Journal of Medicine & Science in Sports, 2002)
Background: Blood testing is a major concern in sports. Sporting federations have introduced cut-off values for hematological variables to limit blood manipulations. Do date, no reference margins have been established to adjust single- or multivariable blood tests to the exercise adapted blood cell system of athletes. We studied hemoglobin (Hb), hematocrit (Hct), blood cell variables and changes in vascular volumes in male and female national team cyclists to evaluate the influence of exercise on these variables and the results of blood tests, and to estimate normal ranges in athletes for blood tests. Methods: 1628 blood samples of 169 male and 55 female athletes were considered. Samples were analyzed automatically, blood cell indices and vascular volumes were calculated. Overall averages and seasonal differences were estimated. Results: Hb-average was: 15.4 +/- 0.8 g dL-1 for male and 13.9 +/- 0.7 g dL-1 for female cyclists, Hct: 45 +/- 2.9% and 40.7 +/- 2.7%. Blood variables and vascular volumes showed significant seasonal changes. 1-6% of all samples were found above the currently used limits for blood testing. This is in accordance with the data from the normal population. Nevertheless, EPO misuse or blood manipulations cannot totally be excluded. Conclusion: Athletes display seasonal adaptations in their blood profile which should be considered in testing regulations. The presented data might be used as reference values for indirect single- and multivariable blood tests.